Contextualization of The Istiṣḥāb Wa Sadd Al-Żarī’ah Towards Islamic Economic Practices in Indonesia - Hendri Hermawan Adinugraha; Fahrodin Fahrodin; Ade Yusuf Mujaddid (Al-'Adl, 2021)
Istiṣḥāb wa sadd al-żarī’ah are two methods of legal decision making in Islam among other methods, whose application always rests on the concept of maṣlahāt. This study describes how the application of istiṣḥāb wa sadd al-’arī’ah to contemporary economic problems in Indonesia. This research is a research library. Data sources are literature or come from various literatures, including books, journals, newspapers, documents, etc. which are relevant to the contextualization of istiṣḥāb wa sadd al-żarī’ah in Islamic economic practices in Indonesia. Data collection techniques in this study used editing, organizing, and finding. Data analysis in this study used deductive and interpretive methods. The results showed that the method of istiṣḥāb wa sadd al-żarī’ah is still very relevant for contextualizing Islamic law in Indonesia in the midst of efforts to oppose social change in facing the challenges of the times, especially in fields related to social and economic practices in Indonesia. Its application still refers to the objectives of Islamic law (maqāṣid al-syarī’ah) and always takes into account the values of mafsadāt and maṣlahāt in istinbaṭ al-hukm.